Building a Cyber Constitution Based on Pancasila: Efforts to Preserve Unity Amid the Global Digitalization Flow - Hermanto, Bagus (Badan Pembinaan Ideologi Pancasila, 2025)
In the face of rapid digital globalization, Indonesia must navigate the complexities of preserving national unity while embracing technological advancements. This article explores the concept of a Cyber Constitution rooted in Pancasila, Indonesia’s state ideology, to address emerging challenges in the digital realm. With the rise of misinformation, cybercrimes, privacy violations, and hate speech, the need for a legal framework that balances technological progress with the preservation of Indonesia's democratic values and unity has become increasingly urgent. Through an examination of current legislative efforts, including the ongoing development of cybersecurity and data protection laws, this paper proposes a comprehensive approach to creating a digital governance structure that fosters national harmony in the age of information technology.